The journey from viral hepatitis to hypocythemia: two case reports - Rehman, Hassan Ur; Javed, Ayesha; Tariq, Nabeel; Abbasi, Nida Zeb (Journal of the Pakistan Medical Association, 2023)
Acute viral hepatitis, including hepatitis A, B, E, D, and G, can lead to severe bone marrow suppression due to cytotoxic lymphocytes. The bone marrow suppression causes aplastic anaemia which is mostly unresponsive to immunosuppressive therapy. Such patients require bone marrow transplant for a complete cure. The pancytopenia can evolve during recovery from transaminitis. We are presenting two case reports relating aplastic anaemia with acute viral hepatitis in two young patients—23 and 16 years of age. The 23-year-old female patient had hepatitis A associated with aplastic anaemia whereas the young 16-year-old male patient was diagnosed with Hepatitis E IgG associated aplastic anaemia. Unfortunately, the first patient could not cope with the complications relating to pancytopenia and was unable to reach the bone marrow transplant stage. The second patient did not have a bone marrow transplant but showed an excellent response to immunosuppressive therapy before the transplant and survived.